Pleasantness and Wellbeing in Poem Declamation in European and Brazilian Portuguese Depends Mostly on Pausing and Voice Quality - Barbosa, Plinio A. (Frontiers in Communication, 2022)
This work investigates the relation between the sensations of pleasantness and well-being and the acoustics of poem declamation in two varieties of Portuguese: European and Brazilian. Ten speakers in each variety recited Alberto Caeiro’s poem "Quando vier a primavera" to which dataset the declamation by two actors were added. Ten listeners in each variety participated in three perception tests for (1) evaluating the degree of pleasantness and well-being of the entire reading in two different sessions by using a 5-degree Likert scale, and (2) choosing the more pleasant recitation from two recitations of a chunk of the poem. Both reciters and listeners were balanced in gender. A set of 22 prosodic parameters was used for predicting the listeners' evaluations in logistic regression models and Linear Discriminant Analysis. Results showed that parameters related to pause and voice quality are the main explanatory variables with a minor role for F0 median. Actors' recitations are preferred and gender-differences are related to reciters, not listeners. Minor differences across the varieties were found.